Embalagens de cigarro: novas estratégias antitabaco - SILVA, Eduarda Eline Coelho da (2018)
This study aims to characterize the approach of the various types of pro and antitobacco advertising, focusing mainly in the following question: Is there still where to make any more progress regards to Brazilian public polices focused in advertising for stopping tobacco? The main objective is to propose new strategies to combat smoking with emphasis on the use of the cigarette packaging itself. All based on researches about the history of the cigarette, as well as its advertising and antismoking laws; and literature on consumer behavior, social psychology, strategic communication, image and design. This way, the defended hypothesis is that the cigarette package still can be better explored than it is right now when it comes to propagate the cigarette evils. The methodology has a descriptive and analytical focus. The relevance of the study is due to the importance of the fight for the reduction of smoking in Brazil, because this one according to ANVISA (2014) in 2002 was responsible for 200.000 deaths in Brazil. As theoretical foundation for this work were used authors as Rick Danger (1973) and Michael Solomon (2011).